Metal modified amino silicone rubber membrane as well as preparation method and application thereof
By mixing the metal salt with NH2-PDMS solution, a metal-modified amino silicone rubber film was prepared, which solved the problem of insufficient flux in the existing film, and improved the CO2/N2 separation performance, and was suitable for industrial applications.
Patent Information
- Application Number
- CN202510195727.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The existing NH2-PDMS membranes have insufficient flux in CO2/N2 separation, making it difficult to meet the needs of industrial applications.
A metal-modified aminosilica rubber film was prepared by mixing the metal salt solution with the NH2-PDMS solution and carrying out room temperature cross-linking polymerization. The membrane optimizes the membrane's pore structure by forming coordination between metal and N atoms in NH2-PDMS, and improves flux and selectivity.
Metal-modified amino silicone rubber films show higher permeability rate and selectivity in CO2/N2 separation, taking into account the improvement of flux and optimization of separation performance, and are suitable for industrial-scale CO2 capture.
Smart Images

Figure CN119838439A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane materials, and in particular relates to a metal-modified aminosilicone rubber membrane and a preparation method and application thereof. Background Art
[0002] Environmental problems such as the greenhouse effect caused by excessive CO2 emissions need to be solved urgently. How to control CO2 emissions and capture CO2 efficiently is crucial. Compared with traditional CO2 separation technologies such as absorption and low-temperature separation, membrane separation technology has the characteristics of high efficiency and energy saving, green environmental protection, simple operation, and easy scale-up. Therefore, it has received more and more attention. The core of membrane separation technology is to develop membrane materials with high permeability and high selectivity. According to the type of membrane material, CO2 separation membrane materials can be divided into organic membranes, inorganic membranes, and organic-inorganic hybrid membranes.
[0003] Silicone rubber materials are widely used in gas separation and liquid separation because of their highly elastic morphology and large changes in Si-O-Si bond angles, which make them have good chemical stability and excellent gas permeability. The segment flexibility of silicone rubber membranes gives them high gas permeability, but it also limits the improvement of selectivity. Compared with PDMS membrane materials, NH2-PDMS contains amino groups with good affinity for CO2 in addition to dimethyl side groups similar to PDMS, which is beneficial to the selective adsorption of CO2 and thus optimizes the gas separation performance of the membrane. Considering the actual industrial application, the larger the membrane flux, the more conducive it is to reducing processing costs and improving production efficiency. Therefore, how to further enhance the permeation flux of NH2-PDMS membranes is of great practical significance. Summary of the invention
[0004] In view of the problems existing in the background technology, the present invention provides a metal-modified aminosilicone rubber film and a preparation method thereof.
[0005] The steps of the preparation method of the metal-modified aminosilicone rubber film provided by the present invention are as follows:
[0006] (1) The silicone rubber is dissolved in an n-heptane solvent containing a 2-butyltin-2-laurate catalyst, and then a crosslinking agent 1,4-bis(triethoxysilyl)benzene (BTESB) is added to the mixed solution, and then a metal salt solution dissolved in ethanol is added, and the mixture is placed in a sealed glass bottle and continuously stirred to perform a room temperature crosslinking polymerization reaction to obtain a metal-modified amino silicone rubber casting liquid.
[0007] The silicone rubber is poly[3-((2-aminoethyl)amino)propyl]methyl(dimethyl)siloxane (NH2-PDMS).
[0008] m(NH2-PDMS):m(BTESB):m(2-butyltin-2-laurate)=1:0.1-0.3:0.01-0.03.
[0009] The metal salts are: cobalt nitrate hexahydrate, nickel nitrate hexahydrate, and lanthanum nitrate hexahydrate, and the mass ratio of the metal salt solution to NH2-PDMS is 0.001-0.0075:1.
[0010] The cross-linking polymerization reaction time is 10-15h, and the viscosity of the obtained silicone rubber casting liquid is controlled to be 40cp-45cp.
[0011] (2) The metal-modified aminosilicone rubber casting liquid is coated on a PAN support as a separation layer, dried at room temperature, and then heat-treated to obtain a metal-modified aminosilicone rubber membrane.
[0012] The method for coating the metal-modified amino silicone rubber casting liquid is a scraping method. The support is cut into a suitable size and placed on a clean glass plate, and deionized water is dripped on the surface. The deionized water on the surface is gently wiped off with dust-free paper and set aside for use. The casting liquid is then scraped on the PAN support to prepare a film.
[0013] The average pore size of the PAN support is 25 nm.
[0014] The heat treatment temperature is: 60-120°C, and the heat treatment time is: 6-10h.
[0015] The application of the metal-modified aminosilicone rubber membrane prepared by the method of the present invention in gas separation is specifically to use the metal-modified aminosilicone rubber membrane for CO2 / N2 separation.
[0016] Beneficial effects of the present invention:
[0017] The present invention provides a metal-modified aminosilicone rubber membrane, which uses NH2-PDMS as a monomer and BTESB as a cross-linking agent. The NH2-PDMS material is modified by metal, so that the separation performance of the membrane is further improved, and the pore structure of the membrane is optimized, so that the prepared metal-modified aminosilicone rubber membrane has a looser network structure, and can improve the flux of the membrane and the CO2 / N2 separation selectivity without changing the original membrane network structure. By optimizing the metal material structure, a composite membrane material with the best separation performance is obtained.
[0018] In addition, the metal will coordinate with the N atoms in the NH2-PDMS membrane, resulting in changes in the overall structure of the membrane and increasing the d spacing of the membrane, thereby increasing the permeation rate of the membrane. Metals usually have high thermal stability, and doped metals can limit the movement of polymer chains to a certain extent, helping to maintain the integrity and stability of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:
[0020] Figure 1 Fourier transform infrared spectra of PDMS, NH2-PDMS and metal-modified NH2-PDMS (wherein, 1—PDMS; 2—NH2-PDMS; 3—CO-NH2-PDMS; 4—Ni-NH2-PDMS; 5—La-NH2-PDMS);
[0021] Figure 2 X-ray photoelectron spectra (full spectra) of PDMS, NH2-PDMS and metal-modified NH2-PDMS materials (wherein, 1—PDMS; 2—NH2-PDMS; 3—Co-NH2-PDMS; 4—Ni-NH2-PDMS; 5—La-NH2-PDMS);
[0022] Figure 3 X-ray photoelectron spectra (Si2p fine spectra) of PDMS, NH2-PDMS and metal-modified NH2-PDMS materials (wherein, 1—PDMS; 2—NH2-PDMS; 3—Co-NH2-PDMS; 4—Ni-NH2-PDMS; 5—La-NH2-PDMS);
[0023] Figure 4 X-ray photoelectron spectra (N1s fine spectra) of PDMS, NH2-PDMS and metal-modified NH2-PDMS materials (wherein, 1—PDMS; 2—NH2-PDMS; 3—Co-NH2-PDMS; 4—Ni-NH2-PDMS; 5—La-NH2-PDMS);
[0024] Figure 5 X-ray photoelectron spectra (Co2p fine spectra) of PDMS, NH2-PDMS and metal-modified NH2-PDMS materials (including 2—NH2-PDMS; 3—Co-NH2-PDMS). DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0026] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0027] The silicone rubber used in the present invention corresponds to the following abbreviations:
[0028] Polydimethylsiloxane (PDMS) and poly[3-((2-aminoethyl)amino)propyl]methyl(dimethyl)siloxane (NH2-PDMS).
[0029] In the scheme of the present invention, the metal-modified aminosilicone rubber membrane is used for the separation of CO2 / N2, referring to the following method: the membrane is placed in a membrane assembly, connected to a gas cylinder, and the CO2 / N2 flux and CO2 / N2 selectivity of different membranes are measured at a CO2 / N2 feed pressure of 100 kPa and a feed temperature of 25°C.
[0030] Example 1
[0031] 1) Preparation of Co-NH2-PDMS casting solution
[0032] 0.529g NH2-PDMS silicone rubber was dissolved in 9.9947g n-heptane, 0.0053g 2-butyltin-2-laurate catalyst was added, 0.0529g BTESB crosslinker was added to the mixed solution, and then ethanol-dissolved cobalt nitrate hexahydrate solution (cobalt nitrate hexahydrate mass was 0.002645g) was added, and the mixture was stirred continuously for 12h in a sealed glass bottle at room temperature for crosslinking polymerization reaction until a suitable viscosity (40cp~45cp) was reached, and Co-NH2-PDMS casting solution was prepared. In this process, m(NH2-PDMS):m(BTESB):m(2-butyltin-2-laurate)=1:0.1:0.01, and the mass ratio of cobalt nitrate hexahydrate to NH2-PDMS silicone rubber was 0.005:1.
[0033] 2) Preparation of silicone rubber membrane
[0034] The experiment uses PAN with an average pore size of 25nm as the support. When using it, the support needs to be cut into a suitable size (one decimeter) and then placed on a clean glass plate, and deionized water is dripped on the surface, and then the deionized water on the surface is gently wiped off with dust-free paper for standby use. The Co-NH2-PDMS casting liquid is used as a separation layer, and a film (about 20μm) is prepared on the PAN support by scraping method, dried at room temperature, and then placed in a 60℃ oven for 6h to obtain a Co-NH2-PDMS membrane.
[0035] Example 2
[0036] This embodiment is different from Embodiment 1 in that the cobalt nitrate hexahydrate is replaced with the same mass of nickel nitrate hexahydrate in step 1) to obtain the membrane of this embodiment, which is recorded as Ni-NH2-PDMS membrane.
[0037] Example 3
[0038] This embodiment is different from Embodiment 1 in that the cobalt nitrate hexahydrate is replaced with the same mass of lanthanum nitrate hexahydrate in step 1) to obtain the membrane of this embodiment, which is recorded as La-NH2-PDMS membrane.
[0039] The gas separation performance of the composite membranes prepared in Examples 1-3 was tested at a feed pressure of 100 kPa and a feed temperature of 25° C. The results are shown in Table 1.
[0040] Table 1 CO2, N2 flux and CO2 / N2 selectivity of membranes doped with different metals at a feed pressure of 100 kPa and a feed temperature of 25 °C
[0041]
[0042] It can be seen from Table 1 that when the added metals are Co, Ni, and La, the CO2 permeation rates are 4.01×10 -6 mol / (m 2 ·s·Pa)、3.68×10 -6 mol / (m 2 ·s·Pa)、3.15×10 -6 mol / (m 2 ·s·Pa), and the CO2 / N2 selectivity was 11. The addition of the three metals caused the permeation rates of CO2 and N2 to show a significant increase. This is because with the addition of metals, the metals and the N atoms in the NH2-PDMS membrane produced a coordination effect, which led to changes in the overall structure of the membrane and increased the d spacing of the membrane, thereby increasing the permeation rate of the membrane.
[0043] Example 4
[0044] This embodiment is different from the embodiment 1 in that the content of the metal added in step 1 is adjusted, that is, a cobalt nitrate hexahydrate solution dissolved in ethanol (the mass of cobalt nitrate hexahydrate is 0.000529 g) is added, and the mass ratio of cobalt nitrate hexahydrate to NH2-PDMS silicone rubber is 0.001:1. The membrane of this embodiment is obtained, and the membrane is recorded as 0.1wt% Co-NH2-PDMS membrane.
[0045] Example 5
[0046] This embodiment is different from the embodiment 1 in that the content of the metal added in step 1 is adjusted, that is, a cobalt nitrate hexahydrate solution dissolved in ethanol (the mass of cobalt nitrate hexahydrate is 0.0013225 g) is added, and the mass ratio of cobalt nitrate hexahydrate to NH2-PDMS silicone rubber is 0.0025:1. The membrane of this embodiment is obtained, and the membrane is recorded as 0.25wt% Co-NH2-PDMS membrane.
[0047] Example 6
[0048] This embodiment is different from the embodiment 1 in that the content of the metal added in step 1 is adjusted, that is, a cobalt nitrate hexahydrate solution dissolved in ethanol (the mass of cobalt nitrate hexahydrate is 0.0039675 g) is added, and the mass ratio of cobalt nitrate hexahydrate to NH2-PDMS silicone rubber is 0.0075:1. The membrane of this embodiment is obtained, and the membrane is recorded as 0.75wt% Co-NH2-PDMS membrane.
[0049] The gas separation performance of the composite membranes prepared in Example 1 and Examples 4-6 was tested at a feed pressure of 100 kPa and a feed temperature of 25° C. The results are shown in Table 2.
[0050] Table 2 CO2, N2 flux and CO2 / N2 selectivity of membranes with different Co ratios at feed pressure of 100 kPa and feed temperature of 25 °C
[0051]
[0052]
[0053] It can be seen from Table 2 that when the added Co ratio is 0.10wt%, 0.25wt%, 0.50wt%, and 0.75wt%, the CO2 permeation rate is 2.89×10 -6 mol / (m 2 ·s·Pa)、3.64×10 -6 mol / (m 2 ·s·Pa)、4.01×10 -6 mol / (m 2 ·s·Pa)、3.71×10 -6 mol / (m 2 ·s·Pa), CO2 / N2 selectivity is 11, 11, 12, 11 respectively. With the increase of Co ratio, the permeation rate of CO2 and N2 increases first and then decreases. This is because when the added Co ratio exceeds 0.50wt%, it has reached saturation. Theoretically, one Co atom can coordinate with 6 -NH2, so the permeation rate when it increases to 0.75wt% is slightly lower than that when it is 0.50wt%.
[0054] Comparative Example 1
[0055] 1) Preparation of NH2-PDMS casting solution
[0056] 0.529g NH2-PDMS silicone rubber was dissolved in 9.9947g n-heptane, 0.0053g 2-butyltin-2-laurate catalyst was added, and 0.0529g BTESB crosslinking agent was added to the mixed solution, and the mixture was stirred continuously for 12h in a sealed glass bottle at room temperature for crosslinking polymerization reaction until a suitable viscosity (40cp~45cp) was reached, and NH2-PDMS casting solution was prepared. In this process, m(NH2-PDMS):m(BTESB):m(2-butyltin-2-laurate)=1:0.1:0.01.
[0057] 2) Preparation of silicone rubber membrane
[0058] The experiment uses PAN with an average pore size of 25nm as the support. When using it, the support needs to be cut into a suitable size (one decimeter) and then placed on a clean glass plate, and deionized water is dripped on the surface, and then the deionized water on the surface is gently wiped off with dust-free paper for standby use. The NH2-PDMS casting liquid is used as a separation layer, and the film is prepared by scraping on the PAN support by scraping, dried at room temperature, and then placed in a 60℃ oven for 6 hours to obtain the NH2-PDMS membrane.
[0059] The gas separation performance of the composite membranes prepared in Example 1 and Comparative Example 1 was tested at a feed pressure of 100 kPa and a feed temperature of 25° C. The results are shown in Table 3.
[0060] Table 3 CO2, N2 flux and CO2 / N2 selectivity of membrane at feed pressure of 100 kPa and feed temperature of 25 °C
[0061]
[0062] Comparative Example 2
[0063] 1) Preparation of Co-PDMS casting solution
[0064] 0.529g PDMS silicone rubber was dissolved in 9.9947g n-heptane, 0.0053g 2-butyltin-2-laurate catalyst was added, 0.0529g BTESB crosslinker was added to the mixed solution, and then ethanol-dissolved cobalt nitrate hexahydrate solution (cobalt nitrate hexahydrate mass was 0.002645g) was added, and the mixture was stirred continuously for 12h in a sealed glass bottle at room temperature for crosslinking polymerization reaction until a suitable viscosity (40cp~45cp) was reached, and Co-PDMS casting solution was prepared. In this process, m(PDMS):m(BTESB):m(2-butyltin-2-laurate)=1:0.1:0.01, and the mass ratio of cobalt nitrate hexahydrate to PDMS silicone rubber was 0.005:1.
[0065] 2) Preparation of silicone rubber membrane
[0066] The experiment uses PAN with an average pore size of 25nm as the support. When using it, the support needs to be cut into a suitable size (one decimeter) and then placed on a clean glass plate, and deionized water is dripped on the surface, and then the deionized water on the surface is gently wiped off with dust-free paper for standby use. The Co-PDMS casting liquid is used as a separation layer, and the film is prepared by scraping on the PAN support by scraping, dried at room temperature, and then placed in a 60℃ oven for 6 hours to obtain a Co-PDMS membrane.
[0067] The gas separation performance of the composite membranes prepared in Example 1 and Comparative Example 2 was tested at a feed pressure of 100 kPa and a feed temperature of 25° C. The results are shown in Table 4.
[0068] Table 4 CO2, N2 flux and CO2 / N2 selectivity of membrane at feed pressure of 100 kPa and feed temperature of 25 °C
[0069]
[0070] Comparative Example 3
[0071] The difference between this comparative example and Example 1 is that the metal is introduced by an impregnation method, and the specific steps are as follows:
[0072] 0.529g NH2-PDMS silicone rubber was dissolved in 9.9947g n-heptane, 0.0053g 2-butyltin-2-laurate catalyst was added, and 0.0529g BTESB crosslinking agent was added to the mixed solution, and the mixture was stirred continuously for 12h in a sealed glass bottle at room temperature for crosslinking polymerization reaction until a suitable viscosity (40cp~45cp) was reached, and NH2-PDMS casting solution was prepared. In this process, m(NH2-PDMS):m(BTESB):m(2-butyltin-2-laurate)=1:0.1:0.01.
[0073] The experiment uses PAN with an average pore size of 25nm as the support. When in use, the support needs to be cut into a suitable size (one decimeter) and then placed on a clean glass plate, and deionized water is dripped on the surface, and then the deionized water on the surface is gently wiped off with dust-free paper for standby use. The casting liquid is used as a separation layer, and the film is prepared by scraping on the PAN support by scraping. It is dried at room temperature and then placed in a 60°C oven for 6 hours to obtain the NH2-PDMS membrane. The prepared membrane is immersed in a hexahydrate cobalt nitrate solution dissolved in ethanol (containing 0.002645g of hexahydrate cobalt nitrate) for 12 hours. After natural drying, the NH2-PDMS membrane modified by the immersion method can be obtained.
[0074] The gas separation performance of the composite membranes prepared in Example 1 and Comparative Example 3 was tested at a feed pressure of 100 kPa and a feed temperature of 25° C. The results are shown in Table 5.
[0075] Table 5 CO2, N2 flux and CO2 / N2 selectivity of membrane at feed pressure of 100 kPa and feed temperature of 25 °C
[0076]
[0077]
[0078] Comparative Example 4
[0079] The difference between this comparative example and Example 1 is that 1,2-bis(triethoxysilyl)methane (BTESM) is selected as a cross-linking agent, and the remaining steps and processes are all referred to Example 1 to obtain the film of this comparative example.
[0080] The gas separation performance of the composite membranes prepared in Example 1 and Comparative Example 4 was tested at a feed pressure of 100 kPa and a feed temperature of 25° C. The results are shown in Table 6.
[0081] Table 6 CO2, N2 flux and CO2 / N2 selectivity of membrane at feed pressure of 100 kPa and feed temperature of 25 °C
[0082]
[0083] In summary, the present invention provides a method for preparing a metal-modified aminosilicone rubber membrane. The present invention preferably uses an amino material modification having an affinity for CO2, which is beneficial to the selective adsorption of CO2, thereby optimizing the gas separation performance of the membrane. Furthermore, by doping with metal materials, the flux of the membrane is further increased, which can significantly improve production efficiency and reduce costs in industrial applications.
[0084] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a metal-modified aminosilicone rubber film, characterized in that: The preparation method steps are as follows: (1) dissolving the aminosilicone rubber in a solvent containing a catalyst, adding a crosslinking agent thereto, and then adding a metal salt solution dissolved in ethanol, placing the solution in a sealed glass bottle and continuously stirring the solution to perform a crosslinking polymerization reaction, thereby obtaining a metal-modified aminosilicone rubber casting solution; (2) The metal-modified aminosilicone rubber casting liquid is coated on a PAN support as a separation layer, dried at room temperature, and then heat-treated to obtain a metal-modified aminosilicone rubber membrane.
2. The method for preparing the metal-modified aminosilicone rubber film according to claim 1, characterized in that: The amino silicone rubber is: poly[3-((2-aminoethyl)amino)propyl]methyl(dimethyl)siloxane NH2-PDMS, and its structural formula is as follows:
3. The method for preparing the metal-modified aminosilicone rubber film according to claim 1, characterized in that: The catalyst is 2-butyltin-2-laurate, the solvent is n-heptane, the crosslinking agent is 1,4-bis(triethoxysilyl)benzene BTESB, and the m(NH2-PDMS):m(BTESB):m(2-butyltin-2-laurate)=1:0.1-0.3:0.01-0.
03.
4. The method for preparing the metal-modified aminosilicone rubber film according to claim 1, characterized in that: The metal salts are: cobalt nitrate hexahydrate, nickel nitrate hexahydrate, lanthanum nitrate hexahydrate, the mass ratio of the metal salt solution to NH2-PDMS is 0.001-0.0075:1, and the obtained metal-modified amino silicone rubber casting liquid has a viscosity of 40cp-45cp.
5. The method for preparing the metal-modified aminosilicone rubber film according to claim 1, characterized in that: The cross-linking polymerization reaction is: reacting at room temperature for 10-15 hours.
6. The method for preparing the metal-modified aminosilicone rubber film according to claim 1, characterized in that: The method for coating the casting liquid is: cutting the support body PAN and placing it on a clean glass plate, dripping deionized water on the surface, then gently wiping off the deionized water on the surface with dust-free paper, and then scraping the metal-modified amino silicone rubber casting liquid on the PAN support body to prepare a film.
7. The method for preparing the metal-modified aminosilicone rubber film according to claim 1, characterized in that: The average pore diameter of the PAN support is 25 nm.
8. The method for preparing the metal-modified aminosilicone rubber film according to claim 1, characterized in that: The heat treatment temperature is 60-120° C., and the heat treatment time is 6-10 hours.
9. A metal-modified aminosilicone rubber film prepared by the method according to any one of claims 1 to 8.
10. An application of the metal-modified aminosilicone rubber film prepared by the method according to any one of claims 1 to 8, characterized in that: The metal-modified aminosilicone rubber membrane is used for CO2 / N2 separation.
Citation Information
Patent Citations
Polydimethylsiloxane fixed carrier promotion transfer membrane as well as preparation method and application thereof
CN103170254A
Fluoride modified metal ion cross-linked pervaporation membrane, preparation and application
CN117138608A
Amino silicone oil composite membrane as well as preparation method and application thereof
CN117654296A
High selectivity facilitated transport membrane
WO2019040633A1